2023
DOI: 10.1002/smll.202301034
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐Assisted Self‐Assembly of 3D Perovskite Nanocrystals into Chiral Inorganic Quasi‐2D Perovskites (n = 3) with Ligand‐Ratio‐Dependent Chirality Inversion

Abstract: Chiral inorganic quasi‐2D perovskites are prepared by self‐assembling 3D perovskites in solution for the first time. The quasi‐2D perovskite synthesized is a pure‐phase perovskite with <n> = 3 and is periodically arranged, which is a big breakthrough in quasi‐2D inorganic perovskites.  With the individual chiral CsPbBr3 nanocrystals (NCs) assemble into quasi‐2D perovskite, the g‐factor significantly improved (≈5 × 10−3). In addition, the chiroptical activity of quasi‐2D perovskites is explored to be impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…According to the collective effect of assemblies, , decomposition of the assemblies and the breaking of the chiral PNA into smaller subdomains of random orientations led to a weakening of CD absorption to near zero. A recent study on the self-assembly of 3D CsPbBr 3 nanocrystals found that assembly can enhance the chiral signal, while the substitution of surface molecules causes chiral inversion . In this work, the reversal of CD signals indicating the substitution of Pro to Phe affects the chirality of PNA.…”
Section: Resultsmentioning
confidence: 48%
See 3 more Smart Citations
“…According to the collective effect of assemblies, , decomposition of the assemblies and the breaking of the chiral PNA into smaller subdomains of random orientations led to a weakening of CD absorption to near zero. A recent study on the self-assembly of 3D CsPbBr 3 nanocrystals found that assembly can enhance the chiral signal, while the substitution of surface molecules causes chiral inversion . In this work, the reversal of CD signals indicating the substitution of Pro to Phe affects the chirality of PNA.…”
Section: Resultsmentioning
confidence: 48%
“…Because of the fact that only l - or d -Phe serves as the ligand during the synthesis process, l - and d -Phe did not exhibit visible CD peaks at around 300 nm . Previous studies have shown that self-assembly of perovskite can induce stronger chiral signals in perovskite . In this regard, the chiral optical activity of PNA may be attributed to assembly enhanced chiral transfer and chiral induction.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…A sequence of diffraction peaks at angles (3.29°, 6.63°, 8.24°, 11.69°, 13.29°, 16.54°) was observed, signifying the emergence of a perovskite QWs with n = 3. [21] Concurrently, discernible periodic diffractions at lower angles indicated an abundance of nanoplatelets stacking within the samples. Moreover, the peaks of BDP-TMA-CsPbBr 3 displayed a low-angle deviation relative to the CsPbBr 3 , suggesting an augmentation in unit cell parameters and volume upon the incorporation of the large BDP-TMA molecule into the layered perovskites.…”
Section: Resultsmentioning
confidence: 91%